Prevalence and Distribution of Cracked Posterior Teeth among Adult Patients (2020)
Background: There are challenges in detection and prevalence of cracked teeth, especially in asymptomatic cases. This underestimates the actual prevalence and possibility of preventive restorative treatment. Objectives: To determine the prevalence and distribution of cracked posterior teeth among adult patients attending the dental clinic of OAUTHC, Ile-Ife, Osun State, Nigeria. Materials and Methods: A cross sectional study where consecutive patients aged 18 years and above were examined for the presence of cracked posterior teeth over a period of one year (May 2016-April 2017). The teeth were initially examined with the naked eye. Thereafter, transillumination, methylene blue dye and magnifying lens were used to aid detection of more cracks. Data was analyzed with the IBM Statistical Package for Social Sciences (SPSS) for Windows (version 21.0). Level of significance was set at p ≤ 0.05. Results: Out of the 64,370 posterior teeth examined for cracks in 3345 patients, 264 were diagnosed as cracked in 152 patients, giving a patient prevalence of 4.5% and tooth prevalence of 0.4%. Amongst the 152 patients, the prevalence was 9.1%. There was a slightly higher male preponderance while cracked tooth was observed to increase with age (p = 0.007). The skilled (56.6%) and those that attained tertiary education (77.6%, p = 0.023) had more cracked teeth. Mandibular first molar (19.7%) was the most frequently cracked tooth type. The cracks were usually centrally placed (91.7%) and run in a mesiodistal direction (61%). Transillumination (44.7%) detected more cracked teeth. Conclusion: Prevalence of cracked tooth was observed to be low with a slightly higher proportion in male and the figure increases with age. Mandibular first molar was the most frequently cracked tooth while transillumination was the most useful diagnostic tool. Most cracks ran in the mesiodistal direction and fracture lines were usually centrally placed.